2009
DOI: 10.1007/s10551-009-0352-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Confucian Work Ethics on Learning About Science and Technology Knowledge and Morality

Abstract: Confucian work ethics, Chinese S&T personnel, innovative cultures, professional quality, morality, knowledge learning,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…For example, Lim (2003) found that CWE were positively associated with individuals" inclination to budget their money. Yeh and Xu (2010) focused on the "Hierarchy and Harmony" dimension of CWE and showed that innovative environments with CWE positively affected learning both general and professional knowledge. Nevertheless, the influence of CWE on workplace deviance behavior has not been empirically examined and analyzed in IS research.…”
Section: Defined By Chinese Cultural Connection (1987) and Rooted In mentioning
confidence: 99%
“…For example, Lim (2003) found that CWE were positively associated with individuals" inclination to budget their money. Yeh and Xu (2010) focused on the "Hierarchy and Harmony" dimension of CWE and showed that innovative environments with CWE positively affected learning both general and professional knowledge. Nevertheless, the influence of CWE on workplace deviance behavior has not been empirically examined and analyzed in IS research.…”
Section: Defined By Chinese Cultural Connection (1987) and Rooted In mentioning
confidence: 99%
“…China has emerged as an economic superpower in the global market. Chinese leadership and management styles are deeply rooted in the country's cultural background (Woods & Lamond, ; Q. Yeh & Xu, ; Zhu, ). Zhu claimed that Confucian ethics influenced the trading fairs and advertisements in commercial industries; these ethics embrace emotions (qing) , rationality ( li ), relationship (guanxi ), and respect ( mianzi ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Confucian virtues have significantly influenced Chinese ethical philosophy in business communities (Q. Yeh & Xu, ). Confucian values include hierarchy and harmony, guanxi, mianzi , group orientation, and time orientation (Q. Yeh & Xu, ). Thompson () suggested the Confucian standard of gentleman‐leader, Junzi , is another business expectation in Chinese society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Learning from negative examples and experiences is part of the process of character education within the context of Confucianism (Low, 2008;Yeh and Xu, 2010). Confucianism declares that it is the function of teachers to provide both positive and negative values and to understand how these values can both affect the individual.…”
Section: Jssmentioning
confidence: 99%
“…Gaining humanity is a major achievement for most people and with the application of personal refinement and self-articulation, it possible to promote propriety (Yeh and Xu, 2010;Lin, 1994). Propriety is based on social roles which protect the rites of life and death.…”
Section: Jssmentioning
confidence: 99%